2013
DOI: 10.1145/2503792.2503797
|View full text |Cite
|
Sign up to set email alerts
|

Information diffusion in online social networks

Abstract: Online social networks play a major role in the spread of information at very large scale and it becomes essential to provide means to analyze this phenomenon. Analyzing information diffusion proves to be a challenging task since the raw data produced by users of these networks are a flood of ideas, recommendations, opinions, etc. The aim of this PhD work is to help in the understanding of this phenomenon. So far, our contributions are the following: (i) a survey of developments in the field; (ii) T-BaSIC, a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
382
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 759 publications
(412 citation statements)
references
References 40 publications
(8 reference statements)
2
382
0
9
Order By: Relevance
“…The calculation of the parameter values using B for the information diffusion process model is shown in Equation (2). b im is obtained from the frequency of community c i , which is paired with a topic t m , divided by the total frequency of all topics paired with c i .…”
Section: Semantic Information Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of the parameter values using B for the information diffusion process model is shown in Equation (2). b im is obtained from the frequency of community c i , which is paired with a topic t m , divided by the total frequency of all topics paired with c i .…”
Section: Semantic Information Flowmentioning
confidence: 99%
“…There have been several studies on information flow modeling based on the structure of social network or the discovery of information diffusion processes without analyzing the structure of There have been several studies on information flow modeling based on the structure of social network or the discovery of information diffusion processes without analyzing the structure of communication [1][2][3][4][5][6]. However, their studies have not shown the relation between context and information flow.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, OSN are represented by graphs in which nodes act as users and edges describes relationships [1]. In OSN exchange of information is growing rapidly and Copyright ⓒ 2017 SERSC various social media like Facebook, Twitter, and LinkedIn etc.…”
Section: Information Diffusionmentioning
confidence: 99%
“…This means that information diffusion is often limited to the immediate neighbours (or n-hops neighbours, with small values of n) of the user who generated the content. Thus, identifying influential nodes covering the role of opinion leaders able to generate large diffusions, and detecting popular topics are important tasks for the analysis and prediction of information diffusion [20]. Based on these remarks, several models have been proposed to simulate information diffusion in OSN [14,17,28,32].…”
Section: Information Diffusion Analysis In Osnmentioning
confidence: 99%